Levels of Structural Integration Mediate the Impact of Metacognition on Functioning in Non-affective Psychosis: Adding a Psychodynamic Perspective to the Metacognitive Approach - Bröcker, Anna-Lena; Bayer, Samuel; Stuke, Frauke; Just, Sandra; Bertram, Gianna; Funcke, Jakob; Grimm, Imke; Lempa, Günter; von Haebler, Dorothea; Montag, Christiane (Frontiers in Psychology, 2020)
Synthetic metacognition is defined by integrative and contextualizing processes of discrete reflexive moments. These processes are supposed to be needed to meet intrapsychic as well as interpersonal challenges and to meaningfully include psychotic experience in a personal life narrative. A substantial body of evidence has linked this phenomenon to psychosocial functioning and treatment options were developed. The concept of synthetic metacognition, measured with the Metacognition Assessment Scale-Abbreviated (MAS-A), rises hope to bridge gaps between therapeutic orientations and shares valuable parallels to modern psychodynamic constructs, especially the ‘levels of structural integration’ of the Operationalized Psychodynamic Diagnosis (OPD-2). As theoretical distinctions remain, aim of this study was to compare the predictive value of both constructs with regard to psychosocial functioning of patients with non-affective psychoses, measured with the International Classification of Functioning, Disability and Health (MINI-ICF-APP). It was further explored if levels of structural integration (OPD-LSIA) would mediate the impact of metacognition (MAS-A) on function (MINI-ICF-APP). Expert ratings of synthetic metacognition (MAS-A), the OPD-2 ‘levels of structural integration’ axis (OPD-LSIA), psychosocial functioning (MINI-ICF-APP) and assessments of general cognition and symptoms were applied to 100 individuals with non-affective psychoses. Whereas both, MAS-A and OPD-LSIA, significantly predicted MINI-ICF-APP beyond cognition and symptoms, OPD-LSIA explained a higher share of variance and mediated the impact of MAS-A on MINI-ICF-APP. Levels of structural integration, including the quality of internalized object representations and unconscious interpersonal schemas, might therefore be considered as valuable predictors of social functioning and as one therapeutic focus in patients with non-affective psychoses. Structural integration might go beyond and form the base of a person’s actual reflexive and metacognitive capabilities. Psychotherapeutic procedures specific for psychoses may promote and challenge a patient’s metacognitive capacities, but should equally take the need for maturing structural skills into account. Modern psychodynamic approaches to psychosis are shortly presented, providing concepts and techniques for the implicit regulation of interpersonal experience and aiming at structural integration in this patient group.